2016
DOI: 10.1111/jcpp.12573
|View full text |Cite
|
Sign up to set email alerts
|

The impact of nonverbal ability on prevalence and clinical presentation of language disorder: evidence from a population study

Abstract: BackgroundDiagnosis of ‘specific’ language impairment traditionally required nonverbal IQ to be within normal limits, often resulting in restricted access to clinical services for children with lower NVIQ. Changes to DSM‐5 criteria for language disorder removed this NVIQ requirement. This study sought to delineate the impact of varying NVIQ criteria on prevalence, clinical presentation and functional impact of language disorder in the first UK population study of language impairment at school entry.MethodsA po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
594
7
56

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 724 publications
(684 citation statements)
references
References 30 publications
27
594
7
56
Order By: Relevance
“…; Norbury et al . ; Tomblin et al . ) and lower than the prevalence found in previous Swedish studies (Miniscalco Mattsson et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…; Norbury et al . ; Tomblin et al . ) and lower than the prevalence found in previous Swedish studies (Miniscalco Mattsson et al .…”
Section: Discussionmentioning
confidence: 99%
“…Norbury et al . () found that 7.58% of 4‐year‐olds had LD of unknown origin (i.e., DLD). In Swedish studies, prevalence figures for LD reported are 10.3% of 2.5‐year‐olds (Miniscalco Mattsson et al .…”
Section: Introductionmentioning
confidence: 99%
“…The Surrey Communication and Language in Education Study (SCALES) used a two‐phase design (Norbury et al., ). In the first phase, reception (kindergarten) class teachers in 263 state‐funded primary schools were invited to complete the Children's Communication Checklist‐Short (CCC‐S, Bishop & Norbury, unpublished), a 13‐item checklist measuring language and communication skills in everyday contexts (maximum score = 39).…”
Section: Methodsmentioning
confidence: 99%
“…Language problems are common in children, with prevalence estimates ranging from 3% to 7%, depending on age and definition (Norbury et al., ; Tomblin, Records et al., ; Weindrich, Jennen‐Steinmetz, Laucht, Esser, & Schmidt, ). In relation to their severity and prevalence, children's language problems receive considerably less research funding than other conditions such as attention deficit hyperactivity disorder (ADHD) or autism spectrum disorder (ASD), with which they frequently co‐occur (Bishop, ).…”
Section: Introductionmentioning
confidence: 99%